Multimodalitas Representasi Laki-Laki pada Iklan Skincare di Media Sosial Instagram Somethinc - Tafrijiyah, Kaamilah; Rahmaida, Hana Fauzia (Jurnal Studi Jurnalistik, 2025)
This study aims to analyze the representation of men in the campaign poster of the beauty product "Somethinc". The method used is a qualitative approach with a descriptive method. Data were collected using purposive sampling, which was then analyzed in conjunction with Kress and Leeuwen's multimodality theory. The data are in the form of advertising poster images obtained from the Instagram social media account Somethinc. The results of the study on the linguistic, visual, spatial, and gestural aspects show that the male figures in the product's advertising poster are portrayed as stylish and charismatic. Keywords: Instagram, advertising, Kress and Leeuwen's multimodality theory, representation, visual communication